Engagement of students in care delivery for individuals with intellectual and developmental disabilities through interprofessional education - Jomy, Jane; Chan, Hillary; McKinlay, Stuart; Mohamed, Sebat; Caplan, Ben; Cohen, Rachel; Caplan, Leigh; Cohen, Lily; Lynch, Jessica; Olesovsky, Shelby; Reissner, Brock (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Implication StatementPatients with intellectual and developmental disabilities (IDD) do not receive quality medical care, resulting in health disparities. A key contributing factor to poor care delivery is the lack of standardized IDD curriculum in Canadian medical education. Many physicians and nurses report they do not feel confident in providing care for patients with IDD. It is imperative to design curriculum for medical and nursing students to build confidence and competency. At the University of Toronto, we delivered a 4-hour workshop that provides a framework for delivering IDD education that should be replicated at institutions Canada-wide to address this critical gap in training.